(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
The successful inclusion of children with cochlear implants in mainstream educational settings largely depends on systematic collaboration between special education teachers (surdopedagogues) and parents. While cochlear implantation provides access to auditory input, the development of functional speech, communicative competence, and academic readiness requires coordinated pedagogical and family support. This article explores effective strategies for preparing children with cochlear implants for inclusive education through structured cooperation between professionals and families. The study analyzes pedagogical principles grounded in socio-cultural theory, particularly the ideas of Lev Vygotsky, emphasizing guided interaction and the role of the social environment in child development. The article highlights the importance of early intervention, auditory-verbal therapy, individualized correctional programs, and consistent home-based reinforcement of speech and listening skills. Special attention is given to parent training, joint goal-setting, continuous monitoring of developmental progress, and the creation of a supportive communicative environment both at home and in school. The findings indicate that effective partnership between surdopedagogues and parents significantly enhances language acquisition, social adaptation, and academic preparedness of children with cochlear implants. The article proposes practical recommendations for organizing collaborative work aimed at ensuring successful integration into inclusive educational settings.